Dimensão territorial da Companhia Paulista de Trens Metropolitanos (CPTM) e suas especificidades organizacionais e laborativas - Medeiros, Renata dos Santos [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
The general purpose of this research was to conduct a geographic analysis of the organization of the Companhia Paulista de Trens Metropolitanos, CPTM, (São Paulo Company of Metropolitan Trains) focusing on their organizational and laboural specific aspects. This work proposed to extend those studies about the consequences of the neoliberal project, adopted and widely spread by the Brazilian government between the end of the 1980 decade and the beginning of 1990. The sectors of infrastructure in Brazil, especially those of the railway industry, started to have marked characteristics of a productive and managerial reorganization which structurally changed the labour relations inside corporations previously run only by the State. In the São Paulo scene, the creation of a company of mixed economy devoted to public transport which would manage the activities of the sector of passengers and would attend to an area of relevant geoeconomic importance consolidated the principles of private investments, in gradual expansion during the 1990 decade. However, an awakening of the real roles of the State took place. The State started to hold the status of both enterprise and entrepreneur in front of the public-private associations and the investments which signalled the emergence of CPTM. Initially we tried to understand how a regional development conditioned the process of urban integration which resulted in the spacialization of the São Paulo Metropolitan Region and we proposed to understand how the most subjective impacts of the productive restructuration process were objected to in the space organization of the metropolis plan ... (Complete abstract click electronic access below)

O objetivo geral desta investigação foi proceder a uma análise geográfica da organização da Companhia Paulista de Trens Metropolitanos - CPTM, focando a investigação em suas especificidades organizacionais e laborativas. Este trabalho buscou ampliar os estudos acerca das consequências do projeto neoliberal adotado e vastamente difundido pelo governo brasileiro entre o final da década de 1980 e início dos anos 1990. Os setores de infra-estrutura no Brasil, entre eles o setor ferroviário passaram a ter características marcantes de uma reorganização produtiva e gerencial que alterou estruturalmente as relações de trabalho no interior das empresas, outrora exclusivamente estatais. No cenário paulista, a criação de uma empresa de economia mista, voltada ao transporte público, que viesse a gerenciar as atividades do setor de passageiros e que atenderia uma região de relevante importância geoeconômica, solidificou os princípios dos investimentos privados, cada vez mais em expansão nas empresas brasileiras na década de 1990. Solidificou-se, todavia, um despertar dos reais papéis do Estado, que passou a garantir um status empresarial e empreendedor frente às parcerias público-privadas e aos investimentos que marcaram o surgimento da CPTM. Buscamos inicialmente compreender como o desenvolvimento regional condicionou o processo de integração urbana, que, por ora resultou na espacialização da Região Metropolitana de São Paulo e nos propusemos a entender como os impactos mais subjetivos do processo de reestruturação produtiva tiveram seus rebatimentos na organização espacial no plano da metrópole ... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Labour; Transport system; Geography of labour; CPTM; Neoliberalism; Companhia Paulista de Trens Metropolitanos; Geografia; Geografia do trabalho; Neoliberalismo; Transporte ferroviario; Geography